ANTIHYPERGLYCEMIC AND ANTIHYPERLIPIDEMIC ACTIVITY OF JATROPHA GOSSYPIFOLIA METHANOLIC EXTRACT IN STREPTOZOTOCIN-NICOTINAMIDE INDUCED DIABETIC RATS - Kumar, Issac Praveen; Malhotra, Ishan; Sundaresan, Sujatha; Dev, Alwin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The objective of the present study is to explore the antihyperglycemic and antihyperlipidemic activities of Jatropha gossypifolia methanolic extract (ME) in streptozotocin (STZ)-nicotinamide (NIC) induced diabetic model. Methods: Type II diabetes was induced by a single dose of NIC (110 mg/kg) and STZ (50 mg/kg b.w.) intraperitoneally. The diabetic animals were treated with ME (50 mg/kg and 100 mg/kg b.w.) of J. gossypifolia. At the end of experimental period, the effect of the ME on creatinine level, triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL) and very LDL (VLDL) were analyzed. Liver function parameters such as glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT) were analyzed and liver glycogen content was estimated spectrophotometrically. After scarification of animals, the liver was collected and subjected to histopathology analysis. Glycogen content was estimated spectrophotometrically. Results: The ME treated diabetic rats showed a significant increase in HDL level and a decrease in creatinine, TG, TC, and VLDL levels. The treated group showed a significant decrease in liver function parameters such as GOT and GPT levels and significantly increased the liver glycogen content. Conclusion: These findings demonstrate that ME possess antihyperglycemic and antihyperlipidemic activity against STZ - NIC induced diabetic rats.